Maximum likelihood-based estimation of diffusion coefficient is quick and reliable method for analyzing estradiol actions on surface receptor movements - Makkai, Geza; Abraham, Istvan M.; Barabas, Klaudia; Godo, Soma; Ernszt, David; Kovacs, Tamas; Kovacs, Gergely; Szocs, Szilard; Janosi, Tibor Z. (Frontiers in Neuroinformatics, 2023)
The rapid effects of estradiol on membrane receptors is in the focus of the estradiol research field, however, the molecular mechanisms of these non-classical estradiol actions are poorly understood. Since the lateral diffusion of membrane receptors is an important indicator of their functional, a deeper understanding of the underlying mechanisms of non-classical estradiol actions can be achieved by investigating receptor dynamics. Diffusion coefficient is a crucial and widely used parameter to characterize the movement of receptors in the cell membrane. The aim of this study was to investigate the differences between Maximum likelihood based estimation (MLE) and Mean Square Displacement (MSD) based calculation of diffusion coefficients, to check reliability of MLE. In this work we applied both MSD and MLE of diffusion coefficients from single particle tracking data extracted from simulation as well as from estradiol-treated AMPA receptor trajectories measured in live dPC12 cells. The comparison of the obtained diffusion coefficients revealed the superiority of MLE over the generally used fitting on the MSD curve. Our results suggest the use of the Maximum likelihood-based estimation of diffusion coefficients because as it has a better performance, especially for large localization errors or slow receptor movements.